Perceptions of Dietary Habits and Risk for Type 2 Diabetes among Congolese Immigrants - Daudet Ilunga Tshiswaka; Kelechi D. Ibe-Lamberts; Dyna Miandabu Mulunda; Juliet Iwelunmor (Journal of Diabetes Research)
Objective. To explore the perceptions of dietary habits and type 2 diabetes risk among Congolese immigrants living in the US. Methods. Data were collected from 20 in-depth interviews and photo-elicitation techniques conducted with Congolese immigrants. The PEN-3 cultural model was used as a guide to analyze the data collected. Results. Participants identified positive, existential, and negative perceptions, enablers, and nurturers associated with dietary habits and type 2 diabetes risk. Participants also acknowledged intrinsic cultural ways of understanding and interpreting the interaction between dietary habits and type 2 diabetes risk among the Congolese people which may influence their health-seeking practices. Conclusions. The findings underscore the importance of culture and how sociocultural factors may play a role with designing culturally appropriate interventions aimed at addressing the risk for type 2 diabetes among Congolese immigrants in the US.